[18F]PSMA‐1007 renal uptake parameters: Reproducibility and relationship to estimated glomerular filtration rate. (23rd November 2022) - Valind, Kristian; Jögi, Jonas; Minarik, David; Trägårdh, Elin
Abstract: Background: Scintigraphy with technetium‐99m‐labelled dimercaptosuccinic acid ([ 99m Tc]Tc‐DMSA) is widely used for renal cortical imaging. Uptake of [ 99m Tc]Tc‐DMSA has been shown to correlate with glomerular filtration rate (GFR). Prostate‐specific membrane antigen (PSMA) radiopharmaceuticals used for positron emission tomography (PET) show high renal uptake and are being investigated for renal imaging. [ 68 Ga]Ga‐PSMA‐11 PET parameters have been shown to correlate with estimated GFR (eGFR). The aim of this study was to investigate the relationship between renal [ 18 F]PSMA‐1007 uptake and eGFR. Methods: Hundred and eighty‐five patients underwent PET imaging at 1 and 2 h after injection of 4.0 ± 0.2 MBq [ 18 F]PSMA‐1007. Serum creatinine levels were measured and GFR estimated using the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) and Modification of Diet in Renal Disease (MDRD) equations. Fifteen patients were excluded due to missing or incorrect data. Thus, data from 170 patients were analyzed. Kidneys were segmented in the PET images using a convolutional neural network with manual correction. For each kidney, mean standardized uptake value (SUVmean ) and segmentation volume in millilitres were measured. Linear regression analyses were performed with eGFR as the outcome variable. Results: Variation in the eGFR values was explained to a significant degree by SUVmean and renal segmentation volume in both the 1 and 2 h images. This correlation was stronger for CKD‐EPI eGFR (1 h R 2 = 0.64; 2 h R 2 = 0.64) than for MDRD eGFR (1 h R 2 = 0.47; 2 h R 2 = 0.45). Conclusion: Renal [ 18 F]PSMA‐1007 uptake parameters correlate with eGFR and are indicative of renal cortical function.